Evaluation of a Mindfulness-Based Intervention With and Without Virtual Reality Dialectical Behavior Therapy® Mindfulness Skills Training for the Treatment of Generalized Anxiety Disorder in Primary Care: A Pilot Study - Navarro-Haro, María V.; Modrego-Alarcón, Marta; Hoffman, Hunter G.; López-Montoyo, Alba; Navarro-Gil, Mayte; Montero-Marin, Jesús; García-Palacios, Azucena; Borao, Luis; García-Campayo, Javier (Frontiers in Psychology, 2019)
Generalized Anxiety Disorder (GAD) is a very prevalent disorder in primary care (PC). Most patients with GAD never seek treatment, and those who do seek treatment often drop out before completing treatment. Although it is an understudied treatment, Mindfulness-Based Interventions (MBIs) indicate preliminary efficacy for the treatment of GAD symptoms, but many patients with GAD present other associated symptoms (e.g. attention deficits) that complicate the treatment. Virtual Reality DBT® Mindfulness Skills learning has recently been developed to make learning mindfulness easier for patients with emotion dysregulation who have trouble concentrating. Virtual Reality (VR) might serve as a visual guide for practicing mindfulness as it gives patients the illusion of “being there” in the 3D computer generated world. The main goal of this study was to evaluate the effect of two MBIs (a MBI in a group setting alone and the same MBI plus 10 minute VR DBT® Mindfulness skills training) to reduce GAD symptoms. A secondary aim was to explore the effect in depression, emotion regulation, mindfulness, and interoceptive awareness. Other exploratory aims regarding the use of VR DBT® Mindfulness skills were also carried out. The sample was composed of 42 patients (roughly half in each group) with GAD attending PC visits. After treatment, both groups of patients showed significant improvements in General Anxiety Disorder measured by the GAD-7 using mixed regression models [MBI alone (B = -5.70; p < 0.001; d = -1.36), MBI+VR DBT® Mindfulness skills (B = -4.38; p < 0.001; d = -1.33)]. Both groups also showed significant improvements in anxiety, depression, difficulties of emotion regulation and several aspects of mindfulness and interoceptive awareness. Patients in the group that received additional 10 minute VR DBT® Mindfulness Skills training were significantly more adherent to the treatment than those receiving only standard MBI (100% completion rate in MBI+VR vs. 70% completion rate in MBI alone; Fisher = 0.020). Although randomized controlled studies with larger samples are needed, this pilot study shows preliminary effectiveness of MBI to treat GAD, and preliminary evidence that adjunctive VR DBT® Mindfulness Skills may reduce dropouts.